2020
DOI: 10.1186/s12879-020-05099-z
|View full text |Cite
|
Sign up to set email alerts
|

Is distance associated with tuberculosis treatment outcomes? A retrospective cohort study in Kampala, Uganda

Abstract: Background: Challenges accessing nearby health facilities may be a barrier to initiating and completing tuberculosis (TB) treatment. We aimed to evaluate whether distance from residence to health facility chosen for treatment is associated with TB treatment outcomes. Methods: We conducted a retrospective cohort study of all patients initiating TB treatment at six health facilities in Kampala from 2014 to 2016. We investigated associations between distance to treating facility and unfavorable TB treatment outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
2
12
2
Order By: Relevance
“…Our findings complement previous studies which found that reduced geographic accessibility is associated with poorer TB diagnostic indicators, adherence, and treatment outcomes ( Robsky et al, 2020 , Shargie et al, 2007 , Tripathy et al, 2013 ). Studies in Ethiopia, Malawi, and Asia found associations between reduced geographic accessibility of health facilities and both TB diagnostic delays ( Cai et al, 2015 , Tadesse et al, 2013 ) and lower case notification rates ( Bui et al, 2018 , Dangisso et al, 2015 , MacPherson et al, 2019 , Shaweno et al, 2017 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings complement previous studies which found that reduced geographic accessibility is associated with poorer TB diagnostic indicators, adherence, and treatment outcomes ( Robsky et al, 2020 , Shargie et al, 2007 , Tripathy et al, 2013 ). Studies in Ethiopia, Malawi, and Asia found associations between reduced geographic accessibility of health facilities and both TB diagnostic delays ( Cai et al, 2015 , Tadesse et al, 2013 ) and lower case notification rates ( Bui et al, 2018 , Dangisso et al, 2015 , MacPherson et al, 2019 , Shaweno et al, 2017 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our finding is consistent with other studies in urban settings in Iran and Canada that found that Euclidean distance-based measures were not well correlated with those on the basis of networks, and therefore, if possible, Euclidean distance should not be used as a proxy for geographic accessibility in place of a network distance ( Apparicio et al, 2017 , Masoodi et al, 2015 ). However, two other urban studies in Durban, South Africa, and Kampala, Uganda found little difference between Euclidean distance and network travel time as predictors of HIV virologic failure among ART users ( Chen et al, 2019 ) and TB outcomes ( Robsky et al, 2020 ), respectively. Another Canadian study in Montreal concluded that using Euclidean distance as a proxy for network distance can introduce substantial errors when considering the city periphery ( Apparicio et al, 2003 ).…”
Section: Discussionmentioning
confidence: 91%
“…We anticipate that with a larger sample size, this finding might be significant. This result is consistent with the findings of an earlier study in Kampala, Uganda that report a trend towards increased mortality among people with TB who travel ≥2 km to receive treatment compared to those who travel <2 km [7] .…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have examined other factors that influence TSR such as age, HIV status, and the category of persons with TB, residence, and sex [4] , [5] , [6] . A recent study in Uganda showed distance may negatively influence treatment success but the evidence did not reach statistical significance [7] . In Ethiopia, one study showed that TB case notification and treatment success rates were lower where there was a long-distance between a health facility and patients’ residence [8] .…”
Section: Introductionmentioning
confidence: 97%
“…Our routine monitoring and evaluation show consistently very high agreement with national TB treatment registers. We additionally captured TB patients' household GPS coordinates at the point of registration for TB treatment; most previous studies have attempted to retrospectively geolocate patients' households using physical addresses, a method that is prone to error [34,35]. Our analysis of household to clinic distance was analysed at a continuous scale rather than on a transformed categorical scale with arbitrary value cut-off points [36,37].…”
Section: Discussionmentioning
confidence: 99%